Evaluation of Biochemical Parameters of Rats Fed with Corn Flour Supplemented with Cricket (Acheta gossypii) Proteins - Elijah Edache Ehoche; Akanya Helmina; Adefolalu Funmilola Sherifat (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
African staple diets are mainly of protein-deficient corn. Dried yellow corn was fermented, dried, ground and supplemented with 5% and 10% of cricket (Acheta gossypii) flour. A standard diet of 5% and 10% soybean proteins-based corn flour was also prepared. The diets were fed to albino rats for four weeks. Standard methods for the serum levels of alkaline phosphatase (ALP), aspartate transaminase (AST), alanine transaminase (ALT), total proteins (TP), and albumin were determined in albino rats using 5% and 10% soybean supplemented corn diets as standard diets. The serum levels of ALP, AST, ALP, TP, and albumin in the rats fed with cricket supplemented diets were in the range of the normal healthy animals but were significantly different from the cornflour and soybean supplemented diets such that the ALP and AST values of the rats fed on the cornflour significantly decreased over the soybean supplemented and cricket supplemented experimental diets. The ALT activity, TP, and albumin levels of the rats fed the cornflour, and the soybean supplemented diets were significantly lower than those fed on the cricket protein supplemented diet (p <0.05). Supplementing corn with crickets has shown improvement in the nutritional quality of corn, therefore, may be used to solve the malnutrition